Idiopathic Copper Deficiency Myeloneuropathy Resulting in Paraparesis: A Case Report. Issue 5 (11th February 2019) - Huang, Kevin; Lee, Debbie; Ingraham, Benjamin; Hijaz, Tarek A.; Anschel, Alan S.
Abstract: Atraumatic spinal cord injuries can be due to inflammatory, vascular, and nutritional etiologies. Due to progression from these causes, the identification and initiation of appropriate treatment are of significant importance. This article explores a case of copper deficiency myeloneuropathy in a patient initially thought to have an inflammatory transverse myelitis. The lack of response to antirheumatologic interventions prompted an extensive workup consistent with copper deficiency. This case stresses the importance of evaluating nutritional causes of myeloneuropathy. Level of Evidence: V